Digitalization of Traditional Markets in Indonesia: Measuring the Impact of Government E-Marketplace Applications on Merchant Financial Turnover and Inclusion (Structural Equation Modeling - SEM Approach) - Jupita Sekar Arum (Al-Makki Publisher, 2023)
The wave of digital transformation and competition with private e-commerce threatens the existence of Indonesia's traditional market. In response, the government launched a special e-marketplace application to digitize traders' operations. However, the effective impact of such applications on traders' economic performance and financial inclusion has not been comprehensively measured. This study aims to analyze the factors that affect the adoption of government e-marketplace applications and measure the direct and indirect impact of their use on increasing the turnover of traditional traders by examining the role of financial inclusion as a mediator. This quantitative research uses the Structural Equation Modeling (SEM) approach. The data was collected through a questionnaire of 300 traditional traders in several major cities who had used government apps. The data analysis technique was carried out by path analysis and mediation test. Perception of usefulness and social support have been shown to significantly affect the use of the app, while ease of use is insignificant. The use of applications has a significant positive impact on increasing turnover, both directly and indirectly. Key findings reveal that financial inclusion acts as a very strong partial mediator, with most of the impact on turnover transmitted through increased access to digital finance. The success of traditional market digitization is highly dependent on the integration of financial features in digital platforms. The implication of the policy is the need to focus on socializing economic benefits, collaboration with financial service providers, and technical assistance for traders. This strategy not only increases turnover but also accelerates financial inclusion in the informal sector.